Multi-scale assessment of the performance-related effects of hydrated lime replacement on SMA mixtures - Carvajal-Munoz, Juan Sebastian (2022)
To gain a deeper insight as to the combined effects of hydrated lime (HL) on asphalt mixtures, a performance-related assessment using a multi-scale approach is thoroughly presented in this dissertation. The experimental work covers an extensive and coherent set of materials, test methods and analytical tools to identify the effects of HL on the mixture response to the main pavement distresses affecting road infrastructures worldwide, which include, rutting, cracking, ageing and moisture-induced damage. In consequence, one of the contributions of this research is producing a comprehensive discussion on the effects of HL through a broad and advanced laboratory characterisation, including bituminous mastics and mixtures, allowing for a deeper understanding of the benefits and limits associated with the use of HL as a partial replacement of Limestone Filler (LF) in SMA mixtures. Furthermore, this research provides insights related to the chemistry and microstructure changes induced by HL on the bituminous mastics, along with detailed comparisons on the rheology of the different material combinations.